The Influence of Product Digital Service Quality “ Laku Pandai” on Customer Satisfaction at Bank Bjb Kcp Cicadas Bandung - Kasino Martowinangun; Gita Dwi Lestari (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to determine the effect of the quality of digital service product “Laku Pandai” on costumer satifaction at Bank BJB KCP Cicadas Bandung. The research method uses descriptive quantitative methods with data collection through field studies and distributing questionnaires. In this study the respondents were customers of Bank BJB by taking a sample of 37 customers. The test was carried out with the Statistical Program for Social Science (SPSS), with the Spearman correlation test and the Spearman validity test, and the results showed the Spearman correlation coefficient value of 0.846 which stated that the influence of the